Intercenter comparison of slow and rapid maxillary expansion in unilateral complete cleft lip and palate - Ayub, Priscila Vaz [UNESP]; Garib, Daniela Gamba; Ebrahim, Hussain; Polido, José; Blasca, Wanderléia; Yen, Stephen (FapUNIFESP (SciELO), 2022)
Objective: The aim of this study was to compare the occlusal changes of rapid maxillary expansion (RME) and slow maxillary expansion (SME) in patients with unilateral complete cleft lip and palate (UCLP), by means of digital dental models. Methods: Group RME was composed by 22 patients (13 males and 9 females), with mean age of 9.9 years, treated with rapid maxillary expansion with Hyrax appliance in Center 1. Group SME was composed by 29 patients (14 females and 15 males), with mean age of 10.7 years, treated with slow maxillary expansion with quad-helix appliance in Center 2. Digital dental models of the maxillary dental arch were obtained immediately pre-expansion (T1) and 6-month post-expansion (T2). Trans-versal distances, arch perimeter, arch length, palatal depth, palatal volume and posterior tooth inclination were digitally measured. Interphase and intergroup comparisons were performed with paired t-test and independent t-test, respectively. Results: Intercanine expansion was 4 to 5mm in both groups, and increase in the intercanine distance was similar for both groups. RME group showed a greater increase in arch distances at the re-gion of permanent premolar and molars, compared to SME group. Arch perimeter increase was greater for RME group, compared to SME. No differences were found for arch length, palatal depth, palatal volume and posterior tooth buccal tipping. Conclusion: RME and SME produced similar dentoalveolar outcomes, with greater amount of expansion on RME group.
Keywords: Cleft lip; Cleft palate; Palatal expansion technique